2022
DOI: 10.1159/000521898
|View full text |Cite
|
Sign up to set email alerts
|

The Link between APOE4 Presence and Neuropsychological Test Performance among Mexican Americans and Non-Hispanic Whites of the Multiethnic Health & Aging Brain Study – Health Disparities Cohort

Abstract: <b><i>Introduction:</i></b> The APOEε4 allele is the single strongest genetic risk for late-onset Alzheimer’s disease (AD). Prior work demonstrates that not only the APOEε4 allele varies by race/ethnicity but also the risk for AD and cognitive impairment conveyed by the APOEε4 allele varies by the racial/ethnic group as well as genetic ancestry. Here, we sought to examine the link between the APOEε4 and neuropsychological functioning among Mexican Americans (MAs). <b><i>Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…In non-HRT users, APOE4 carriers had a 3% lower delayed memory index score than non- APOE4 (Table 2 ). This result is consistent with literature showing that delayed and immediate memory are lower in at-risk APOE4 women [ 25 , 43 , 44 ]. HRT was found to influence cognition in an APOE -dependent manner.…”
Section: Discussionsupporting
confidence: 93%
“…In non-HRT users, APOE4 carriers had a 3% lower delayed memory index score than non- APOE4 (Table 2 ). This result is consistent with literature showing that delayed and immediate memory are lower in at-risk APOE4 women [ 25 , 43 , 44 ]. HRT was found to influence cognition in an APOE -dependent manner.…”
Section: Discussionsupporting
confidence: 93%
“…Our secondary analysis aimed to examine differences for genetic and health risk factors for MCI and AD between Hispanic and NHW ethnicities and included more participants than previous single or meta-analysis studies. [4][5][6][7][8][9] In our combined data set, the proportion of NHW APOEε4 carriers was 41.8% and the proportion of Hispanic APOEε4 and all-cause MCI diagnoses was significantly weaker in Hispanic participants compared to NHW participants, while no association differences between ethnicities were observed for the influence of APOEε4 on AD diagnoses, which is in line with the previous claim that the APOEε4 allele contributed to dementia and poorer memory performance similarly across racial and ethnic groups. 9 We did find a significantly stronger association between APOEε2 and AD diagnoses in Hispanic participants compared to NHW participants, which was contrary to a previous study that reported APOEε2 had the same neuroprotective effects across ethnicities.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies suggested that the presence of APOEε4 was more strongly associated with AD outcomes in NHW participants than in Hispanic participants, 4 that the APOEε4 gene dose effect was not applicable in the Hispanic population, 5 and that the APOEε4 allele was only associated with poor memory performance in Mexican American participants, whereas the APOEε4 allele was associated with poorer memory performance, and worse executive functioning and verbal fluency in NHW participants. 6 More specifically within different Hispanic populations, one study found that APOEε4 associated with significant cognitive decline only in Hispanic participants with a Cuban background. 7 However, other studies have found that APOEε4 contributed to worse cognitive impairment in white Hispanic participants than in NHW participants, 8 or that APOEε4 contributed to dementia and poorer memory performance similarly across racial and ethnic groups when comparing Caribbean Hispanic, Hispanic American, African American, and NHW American participants.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with what we have previously shown, 36,37 the presence APOEε4 is significantly higher in NHWs than MAs. Although the presence of APOEε4 has been linked to poorer performance in multiple cognitive domains in NHWs and poorer memory in MAs 38 , and is a major risk for the development of dementia, there is evidence that APOEε4 positivity does not confer increased risk for depression 39 . Our results are consistent with the lack of a relationship between depressive symptoms and APOEε4 status and this held for both NHWs and MAs.…”
Section: Discussionmentioning
confidence: 99%